O sentido da escola (pública) para o adolescente - Tomio, Noeli Assunta Oro (2010)
This study aimed at describing and analyzing the component elements of the senses and the meanings of the school that are produced daily by teenagers in high school public schools. We focused on the theoretical historical-cultural approach, emphasizing aspects such as the concept of man in a historical-cultural perspective, activity, thought and word, senses and understanding of adolescence and the social role of the school. The methodological procedures were based on qualitative research. The data collected involved three rounds of interaction with a group of teens who were used as a source for data collection. The analysis was based on the understanding of the meanings produced and shared by teenagers about school and getting closer to their zones of sense. Results from observation revealed that the teenager, on one hand, sees the school as a source of knowledge and wisdom, relationships and socialization. There is an ideological sense on the role of the school related to their future, so that the school is meant as a gateway and the only way to ensure the achievement of success personally, professionally and financially. However, the meanings produced are mediated by feelings of anger, frustration and discouragement, because the school does not offer the knowledge they seek. The final thoughts of this research point to the need for a strong educational recovery work through the process of mediation of the activities undertaken by the teacher and students. This involves a dialectical understanding of the subject object, where the man and his social relations are crucial to the development of his psyche, as well as the role of culture in this process